Essentials of Spinal Cord Injury Medicine - Dionyssiotis, Yannis (IntechOpen, 2018)
Spinal cord injury is a severe condition leading to serious neurological dysfunctions and changes a person's life in a sudden way. Understanding the pathophysiology of spinal cord injury will improve the prognosis and reintegration to the society of spinal cord-injured subjects. The book Essentials in Spinal Cord Injury Medicine includes seven chapters with valuable information addressing hot topics related to spinal cord injury, ranging from pathophysiology, nontraumatic spinal cord injury, complications to exoskeletons, and research therapies with mesenchymal stem cells. The book could be a valued reference for physiatrists, neurosurgeons, orthopedic surgeons, neurologists and physical therapists.